PENGARUH TANGGUNG JAWAB SOSIAL TERHADAP BIAYA MODAL PADA PERUSAHAAN LQ-45 DI BURSA EFEK INDONESIA - Batara Alexander Liberty; Fikri Asyrafi; Hilda Nainggolan; Lupita Sari; Farah Margaretha (Jurnal Manajemen, 2021)
Corporate social responsibility (CSR) is a long-term business strategy that is contradictory to one of the company's goals, which is profit, so shareholders are faced with dilemmas and polemics, especially in Indonesia. Therefore, this study was conducted to find evidence whether CSR is able to offer value-added to shareholders by influencing the company's cost of capital which consists of cost of equity and cost of debt. The independent variable used is the cost allocated to support CSR activities. There are six control variables which are systematic risk, price to book ratio, firm size, debt ratio, revenue growth, composition of independent commissioners. The researcher uses data from 22 companies whose shares have been listed on the Indonesia Stock Exchange as LQ-45 for the period 2014-2020 and uses a multiple regression research testing model. The conclusion of this studies indicate that corporate social responsibility has a significant positive effect on the cost of equity and a significant negative effect on the cost of debt. Firm size has a negative effect on both the cost of equity and the cost of debt, while revenue growth has a positive impact on the cost of equity. The debt ratio has a positive effect on the cost of debt. The other variables do not have a significant effect on the cost of capital. This study is expected to be able to help interested parties to predict, control and anticipate the movement of the company's cost of capital'